2022
DOI: 10.1108/ijchm-08-2021-0980
|View full text |Cite
|
Sign up to set email alerts
|

Motivation behind review provision in online travel communities: do hometowner contributions matter?

Abstract: Purpose Online reviews have become increasingly important and numerous studies have noted the effect of social factors on the review provision of users. The purpose of this study is to investigate how hometowner contributions, which are defined as prior reviews posted by users from the same city, affect the quality of reviews by focal users. Design/methodology/approach Based on the theories of competitive altruism, pure altruism and reciprocity, as well as several social influence theories, a conceptual fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Pooling Layer: After feature extraction is completed in the convolutional layer, the resulting feature map is subjected to processing in the pooling layer. The main purpose of the pooling layer is to reduce the size of the feature map, thereby compressing the data and improving the network's ability to generalize [25][26][27]. This layer is also known as the downsampling layer.…”
Section: A Cnnsmentioning
confidence: 99%
“…Pooling Layer: After feature extraction is completed in the convolutional layer, the resulting feature map is subjected to processing in the pooling layer. The main purpose of the pooling layer is to reduce the size of the feature map, thereby compressing the data and improving the network's ability to generalize [25][26][27]. This layer is also known as the downsampling layer.…”
Section: A Cnnsmentioning
confidence: 99%
“…Wang et al (2018) demonstrated the effect of company image on the formation of favorable word-of-mouth associations. Liang et al (2022) reported that various online travel companies use customer reviews to persuade new customers to stay at hotels that are advertised on their mobile applications. Many hotels also offer online incentives to customers who submit reviews.…”
Section: Word-of-mouthmentioning
confidence: 99%